Prediction and Analysis of the Quality of Multimedia Professional Talents Combining Multiobjective Data Fuzzy Evolution. (3rd September 2021) - Luo, Ao; Yang, Yongfeng
Abstract : In response to the relatively huge error, low efficiency, and low accuracy in the prediction and analysis data on the quality of multimedia professional talents at present, an analytical method for the prediction of the quality of multimedia professional talents based on the multiobjective data fuzzy evolutionary algorithm is proposed in this paper. The weights of the talent quality data are analyzed in detail mainly based on the multiobjective data fuzzy evolution algorithm to establish a prediction and analysis model for the quality of multimedia professional talents. This model can be used to implement the prediction and analysis of the comprehensive abilities of multimedia professional talents effectively. Finally, through a practical case study, it is verified that the method put forward in this paper has high efficiency and high accuracy in predicting and analyzing the quality of multimedia professional talents.